2015
DOI: 10.1108/imr-09-2013-0175
|View full text |Cite
|
Sign up to set email alerts
|

The brand origin meaning transfer model (BOMT): an integrative theoretical model

Abstract: Purpose – The purpose of this paper is to explore how brand origin (BO) cues affect the consumer’s association of a new brand with BO learning and the subsequent effects on brand image (BO semiotics). An integrative theoretical framework is proposed that includes both processes. Design/methodology/approach – The proposed model is based on analogical learning theory and triadic semiotic theory. Findings – Two types of BO knowledge form BO meanings in consumer minds: country-related categories and exemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 36 publications
2
20
0
1
Order By: Relevance
“…As a result, the firm can benefit from the image of the home country in developing its brand strategy (D'Antone & Merunka, 2015;orđević, 2008;Herstein et al, 2014). However, any benefit from COI is not automatically gained.…”
Section: Coi As a Csa At The Firm Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the firm can benefit from the image of the home country in developing its brand strategy (D'Antone & Merunka, 2015;orđević, 2008;Herstein et al, 2014). However, any benefit from COI is not automatically gained.…”
Section: Coi As a Csa At The Firm Levelmentioning
confidence: 99%
“…COI investigations have focussed on analysis from a consumer behaviour perspective (Carneiro & Faria, 2016;Peterson & Jolibert, 1995;Usunier, 2006) and offer little information related to strategy (Morello, 2014;Roth & Diamantopoulos, 2009;Samiee, 2010). From the strategic perspective, existing studies analysing COI as a resource provide only an exploratory construct evaluation through a qualitative or conceptual approach (Agrawal & Kamakura, 1999;Baker & Ballington;orđević, 2008;Chattopadhyay, Batra, & Ozsomer, 2012;Cuervo-Cazurra & Un, 2015;D'Antone & Merunka, 2015;Herstein, Berger, & Jaffe, 2014;Kumar & Steenkamp, 2013;Spence & Hamzaoui Essoussi, 2010;Suter et al, 2017). Our study fills this gap by developing a scale for the COI from a managerial perspective, attending Diamantopoulos, Schlegelmilch, and Palihawadana's (2011) call for new studies analysing COI not only as a driver of product image, but also as the guiding image of a brand captured through it.…”
Section: Introductionmentioning
confidence: 99%
“…Table 3 details how each company use those tools. Insert table 3 We could also verify the rise of another tool to incorporate the CI: the use of senses, making the association between CI and brand more experiential (D'Antone & Merunka, 2015). The senses identified in the CI incorporation are the touch in the packaging, the listening/hearing with the adoption of Brazilian songs at the points of contact with the customer and the smell through the use of fragrances from the raw material of the country.…”
Section: Natura and L'occitane Au Brésilmentioning
confidence: 99%
“…To the best of our knowledge, this is the first paper that offers categorised CI tools from a business perspective. From this viewpoint, existing studies analyzing CI incorporation have provided some cues to develop CI on brand (Agrawal & Kamakura, 1999;Spence & Hamzaoui Essoussi, 2010;Baker & Ballington orđević, 2008;Chattopadhyay et al, 2012;Kumar & Steenkamp, 2013;Herstein, Berger, & Jaffe, 2014;Cuervo-Cazurra & Un, 2015;D'Antone & Merunka, 2015), but have not organized them into a framework As a theoretical contribution, the study outlined tools that may help researchers develop new instruments to understand the importance of CI usage in brand strategy. It also showed that in the branding strategy the CI usage could be operationalized using different tools.…”
Section: Final Considerationsmentioning
confidence: 99%
“…Dentre os estudos identificados, nenhum propõe, tampouco testa uma escala para medir a importância ou a forma de uso do país de origem como um recurso na estratégia da empresa, eles apenas fornecem uma avaliação exploratória do construto por meio de uma abordagem qualitativa ou conceitual (ver: Cuervo -Cazurra & Un, 2015;Agrawal & Kamakura, 1999;Baker & Ballington, 2002;Đorđević, 2008;Herstein, Berger & Jaffe, 2014;Kumar & Steenkamp, 2013;Chattopadhyay, Batra & Ozsomer, 2012;Paterlini, Giraldi & Amui, 2012;Castro et al, 2014;Spence & Hamzaoui Essoussi, 2010;D'Antone & Merunka, 2015). Portanto, identificou-se que não há uma escala delineada e validada que mensure a importância da COI como recurso na estratégia da empresa em processo de internacionalização, sendo essa a problemática que o presente estudo buscou sanar.…”
Section: Introductionunclassified